Chinese adolescents' reports of covert parental monitoring: Comparisons with overt monitoring and links with information management. (22nd December 2016) - Hawk, Skyler T.
ABSTRACT: This study compared Chinese adolescents' reports of covert parental monitoring with the overt strategies of solicitation and control. We investigated these behaviors in terms of unique associations with adolescents' perceived privacy invasion and the information management behaviors of disclosure and secrecy. High school students ( N = 455, 61.5% female; M age = 17.39, SD = 0.83) from a predominantly rural province of Mainland China reported a high incidence of covert monitoring (60.40%). Covert monitoring predicted privacy invasion more strongly than solicitation or control. Solicitation positively predicted disclosure, while covert monitoring negatively predicted disclosure and positively predicted secrecy. Privacy invasion fully mediated links between covert monitoring and information management. These latter effects were significantly stronger for girls than for boys. Similar to Western adolescents, Chinese youth might apply selective resistance when parents violate their personal domain. The findings suggest linkage between some parental monitoring behaviors and disruptions in Chinese family communication.